Hepatocyte-Derived Exosomes Promote Liver Immune Tolerance: Possible Implications for Idiosyncratic Drug-Induced Liver Injury. (15th May 2019) - Holman, Natalie S; Church, Rachel J; Nautiyal, Manisha; Rose, Kelly A; Thacker, Sarah E; Otieno, Monicah A; Wolf, Kristina K; LeCluyse, Edward; Watkins, Paul B; Mosedale, Merrie
Abstract: Most idiosyncratic drug-induced liver injury appears to result from an adaptive immune attack on the liver. Recent evidence suggests that the T-cell response may be facilitated by the loss of immune tolerance. In this study, we explored the hypothesis that constitutively released hepatocyte-derived exosomes (HDE) are important for maintaining normal liver immune tolerance. Exosomes were isolated from the conditioned medium of primary human hepatocytes via polymer precipitation. Mock controls were prepared by processing fresh medium that was not hepatocyte exposed with precipitation reagent. THP-1 monocytes were then treated with HDE or an equivalent volume of mock control for 24 h, followed by a 6-h stimulation with LPS. HDE exposure resulted in a significant decrease in the LPS-induced media levels of interleukin-1β and interleukin-8. Gene expression profiling performed in THP-1 cells just prior to LPS-induced stimulation identified a significant decrease among genes associated with innate immune response. MicroRNA (miRNA) profiling was performed on the HDE to identify exosome contents that may drive immune suppression. Many of the predicted mRNA target genes for the most abundant microRNAs in HDE were among the differentially expressed genes in THP-1 cells. Taken together, our data suggest that HDE play a role in maintaining normal liver immune tolerance. Future experiments will explore the possibility that drugs causing idiosyncratic liver injury promote the loss of homeostatic HDE signaling.